(NiGLOTERAPIQ (B:s (N|NERGET(B. (NMETOD LE^ENIQ (B/s - (NmOLOSTOW(B, (NwALERIJ dMITRIEWI^s ((NmOSKWA (B:s (NgRANDs (Nfair(B-(Npress(B,s, 2003)
(NkNIGA SODERVIT SAMU@ POLNU@ INFORMACI@ PO DIAGNOSTIKE I LE^ENI@ BOLEZNEJ S POMO]X@ IGLOTERAPII(B, (NTO ESTX WOZDEJSTWIEM NA WNUTRENN@@ \NERGI@ ^ELOWEKA(B. (NdLQ [IROKOGO KRUGA ^ITATELEJ(B.s
(NbIBLIOGR(B.: (NS(B. 536-537s
Keywords: (NzDRAWOOHRANENIEs; (NiGLOTERAPIQs; (NmEDICINSKIE NAUKI (B- (NoB]AQ TERAPIQs; (NrEFLEKSOTERAPIQs